Alimentação do peixe-de-briga, Betta splendens (Regan, 1910) em tanque externo de cultivo: Dieta natural e formulada - Sipaúba-Tavares, L. H. [UNESP]; Appoloni, A. M. [UNESP]; Fernandes, J. B.K. [UNESP]; Millan, R. N. [UNESP] (FapUNIFESP (SciELO), 2016)
The growth rate and percent survival of Betta splendens when submitted to formulated diet and live food treatments are evaluated. The three different diets were used and designated as: formulated diet (basal diet); live food diet (plankton) and mixed diet (formulated diet with plankton). The live food diet contained plankton belonging to an open pond. High mortality was reported with live food (plankton) treatment whereas higher percent survival occurred with formulated diet. Highest specific growth rate, weight gain and final weight were reported in the mixed diet treatment and were significantly different (p<0.01) from those in formulated diet and live food treatments. The gut contents of B. splendens in mixed diet and live food treatments comprised, Rotifera and Bacillariophyceae species in high percentages or rather, over 78% of total organisms. Lecane sp. was the most ingested zooplankton species by B. splendens in both treatments (mixed diet and live food), with the phytoplankton species Asterionella sp. and Melosira sp. respectively in mixed diet and in live food, respectively. Results indicated that the formulated diet influenced the water parameters dissolved oxygen, total suspended solids, total dissolved solids and pH. The live food in the open pond was not enough to improve the growth rate and percent survival of B. splendens. The growth performance of B. splendens; had the best results with mixed diet which was capable of maintaining species’s survival (82%) and development in artificial conditions, benefiting the culture management of ornamental fish.
Feed of siamese fighting fish, Betta splendens, (Regan, 1910) in open pond: Live and formulated diets
Keywords: Aquaculture; Formulated diet; Growth; Ornamental fish; Plankton